The relationship between creative tourism and local development: a bibliometric approach for the period 2009-2019 - Carlos A. Máximo Pimenta; José Cadima Ribeiro; Paula Cristina Remoaldo (Tourism & Management Studies)
More and more people want to travel to destinations expecting to live unique and active tourist experiences, linked to the culture and traditions of the host communities, and interact with local people. In the concept of creative tourism, these dimensions of proximity to residents, of tourists’ participation in the configuration of their own experience and the expression of creativity based on cultural references and attributes of the destination, are present. It is in this context that multiple researchers have been looking to the creative tourism segment as an opportunity for the development of various territories. The aim of this investigation is to identify the relationship which can be found in the literature between creative tourism and local development, using as research method a bibliometric inventory made in scientific databases (Academia. edu, Econlit, Google Scholar, CAPES Journals, Redalyc, Scielo.org, SCOPUS, and Web of Science, among others). In general, it was possible to verify that there is a concern of the authors of the papers analysed in establishing a link between creative tourism and local/regional development, without however going far on this dimension, or at least identifying impact of economic, cultural, social and environmental nature. This way, it seems to be important that future research goes far in the inventory of the hypothesized relationship between the proposals of creative tourism and the benefits it can bring to local communities.